Hindsight - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series., 2020)
Dr. Kendra Michaels, blind for the first twenty years of her life before gaining her sight via a revolutionary surgical procedure, is a renowned investigator known for her razor-sharp senses--honed during her years in the dark--and keen deductive abilities. Now her skills are needed uncomfortably close to home. Two staff members have been murdered at a school for the blind where Kendra spent her formative years. But the murders are puzzlingly dissimilar: one victim was brutally stabbed, while the other was killed by a bullet to the head. Are the crimes related? Or is Kendra on the hunt for more than one dangerous killer? With the killer (or killers) still on the loose, Kendra must put her life on the line to unravel a terrifying conspiracy. But Kendra soon discovers that she herself may hold the key to the deadliest secret of all...--